Harmonic Effects Analysis of Electronic Loads Controller On Self Excited Induction Generator (SEIG) Operations - Refdinal Nazir; Andi Pawawoi; Riska Amalia (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The aplication of Electonic Load Controller (ELC) on Self-Excited Induction Generator (SEIG) driven by renewable energy sources creates harmonic issues. This paper has analyzed the propagation of the harmonic current generated by the ELC in the generator system. Mathematical modeling and computer simulation is used to analyze the propagation of harmonic currents generated by ELC on the generator system. Laboratory testing has also been conducted to justify the simulation results. The study results showed that the propagation harmonic currents created by ELC on the stator widings of SEIG and main load side are rejected for high order components, and attenuated for lower order components. Consequently, the THDI of stator and main load current will be reduced significantly.